The rhetoric of philosophy - Frogel, Shai (Controversies, 2005)
The book claims that philosophy can be defined by its distinct rhetoric. This rhetoric is shaped by two values: humanism and critique. Humanism is defined as preferring the individual human deliberation to any external authority or method. Self-conviction is the touchstone of truth in philosophy. Critique is defined as suspecting your beliefs and convictions. This is the reason why the book uses Nietzsche's definition of "the will to truth"--"the will not to deceive, not even myself"--for explaining the nature of philosophical thinking and argumentation. This rhetorical analysis reveals that